A 'Low-Road' Approach to the Haitian Apparel Sector - Mats Lundahl; Bengt Söderlund (Lund University, School of Economics and Management, Department of Economics, 2021)
The paper analyzes the need for structural change in the Haitian economy, an economy where the majority make their living in agriculture – a sector characterized by a severe erosion problem. It is argued that tourism does not offer any solution, other than possibly in the long run. The only alternative is export-based industrialization, since Haiti is a small and poor country. Its comparative advantage rests on an abundant supply of unskilled labor and exports are heavily concentrated to the apparel sector. This comparative advantage is reinforced by advantageous access to the United States market. Unfortunately, the expected employment effects have not materialized so far and wages are low in the sector. Still, employment there makes a contribution to the household economy, together with remittances from Haitians abroad. The apparel sector provides employment at a wage which is higher than the one in agriculture or the urban informal sector. Raising wages above the level prevailing in competing countries is difficult, but employment can potentially be expanded, but Haiti's bad business climate does not attract investors. Here, the government plays a central role. Haiti's infrastructure is bad and the Haitian state has always displayed strong predatory features.
Keywords: O10; O14; O54; 330; Haiti; economic development; structural change; apparel industry